1992
DOI: 10.1021/bi00118a028
|View full text |Cite
|
Sign up to set email alerts
|

Cation-dependent transition between the quadruplex and Watson-Crick hairpin forms of d(CGCG3GCG)

Abstract: The DNA oligonucleotide d(CGCG3GCG) can form either a Watson-Crick (WC) hairpin or a parallel-stranded quadruplex structure containing six G-quartet base pair assemblies. The exchange between these forms and single strands can be monitored using circular dichroism (CD). NMR results verified the assignment of specific CD bands to quadruplex and hairpin species, respectively. Cations stabilize the quadruplex in the order K+ greater than Ca2+ greater than Na+ greater than Mg2+ greater than Li+ and K+ greater than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
251
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(283 citation statements)
references
References 48 publications
26
251
1
Order By: Relevance
“…In the presence of 1 mM LiCl, the CD spectrum was not altered as expected because lithium ions do not support the formation of G-quadruplexes (35, 37, 52). In our experiments, addition of 1 mM NaCl also had no effect on G-quadruplex formation, possibly due to the lower propensity of sodium ions compared with potassium ions to stabilize G-quadruplex structures (32,34,35,37,42,52).…”
Section: The 5ј-utr Of Adam10 Contains a G-rich Region Whichmentioning
confidence: 53%
“…In the presence of 1 mM LiCl, the CD spectrum was not altered as expected because lithium ions do not support the formation of G-quadruplexes (35, 37, 52). In our experiments, addition of 1 mM NaCl also had no effect on G-quadruplex formation, possibly due to the lower propensity of sodium ions compared with potassium ions to stabilize G-quadruplex structures (32,34,35,37,42,52).…”
Section: The 5ј-utr Of Adam10 Contains a G-rich Region Whichmentioning
confidence: 53%
“…Different G-quartet isomers form, depending on the DNA strand concentration and cations present (29,30). Intermolecular G-quartets arise from the association of four individual single-stranded G-rich DNA molecules, whereas intramolecular G-quartets are formed from a single strand of G-rich DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Such an error in the determination of torsion corresponds to a difference in 3 J(C8-H1′) couplings equal to 2.2 Hz. Of note, the error due to neglecting the nonplanarity of nucleobases and geometry deformation at C1′ is 5-10-fold larger than typical experimental error in the determination of 3 J (C8-H1′).…”
Section: Discussionmentioning
confidence: 99%
“…27 Two years later, Ippel et al showed that the same KEs also hold qualitatively for adenosines. 28 Using the published NMR data and their own results, Ippel et al reparametrized and generalized the KEs for the 3 J couplings across glycosidic bonds in all DNA and RNA nucleosides. 28 29 Their detailed analysis revealed that the KE by Ippel can be used to discriminate syn and anti nucleosides, but it could Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation